Inovação tecnológica em projetos de novos produtos: um estudo exploratório sobre relações gerenciais de integração entre unidades de uma multinacional - Jugend, Daniel [UNESP]; Silva, Sérgio Luis da (University Nove de Julho, 2012)
Although thetopic of integrationin product development is widely debated in the literature, there are few studies that address the participation by subsidiaries of multinational and R & D centers around the world in development projects of new products. Focusing on the perception of the Brazilian unit, this paper aims to present and analyze integration practices among subsidiaries, headquarters and R&D centers in product development projects in amultinational high tech company. For this purpose, was conducted an exploratory and qualitative researched operationalized by case study. Among the main results, it was noted collaboration betweenlocals marketing and engineering with the R & D centers, important role of senior management in the Brazilian unit to communicate outcomes of the strategic planning of products andtechnologies established by the headquarters to the subsidiary, the adoption of technological and information mechanisms and the application of methods such as technology roadmap.

Apesar do tema integração no desenvolvimento de produtos ser amplamente debatido pela literatura, são poucos os estudos que abordam nas empresas multinacionais a participação de filiais junto a centros de P&D espalhados mundo em projetos de desenvolvimento de novos produtos. Tendo como foco a percepção da unidade brasileira, este artigo visa apresentar e analisar as práticas de integração entre filial, matriz e centros de P&D em projetos de desenvolvimento de produtos em uma empresa multinacional de base tecnológica. Para isso, além de revisão teórica, foi realizada uma pesquisa exploratória, qualitativa, operacionalizada por meio de estudo de caso. Dentre os principais resultados, notou-se que ocorre a colaboração entre o marketing e engenharia local com os centros de P&D, relevante papel da alta administração da unidade brasileira em comunicar resultados do planejamento estratégico de produtos e tecnologias estabelecidos pela matriz à filial, a adoção de mecanismos virtuais de interação e a aplicação de métodos como o technology roadmap.
Technological innovation in projects of new product development: an exploratory study on relationship management integration among units of a multinational company
Keywords: Integration; Technological innovation of products; Multinational company; Integração; Inovação tecnológica de produtos; Empresa multinacional